Studi Ekologi Moluska Bernilai Ekonomi Pada Hutan Mangrove di Teluk Youtefa Kota Jayapura - Tenny Wijayanti; Suriani Br. Surbakti; Samuel J. Renyaan (Jurusan Biologi FMIPA Universitas Cenderawasih, 2013)
Study of ecology of mangrove organisms at Yotefa Bay Jayapura has been done from February to December 2012. The main purpose of this study is to collect the ecological data mangrove organism focus on diversity, distribution, richness, and similarity. The study was on organisms which have economical values for people living at the Papua Trade Centre area (PTC), Skyland, and Nafri. The data were collected with the line transects and quadrate methods, and data was examined with description on quantitative and qualitative methods. The result showed that there were 7 species of mangrove organism which have economical values; which were Anadara granosa, Anadara pilula, Isognomon ephippium, Gelonia erosa, Gelonia expansa, Pinna nobilis, and Faunus ater. The diversity index revealed that the highest number of species diversity was in PTC and Nafri area which were 1,70 and the lowest species diversity was in Skyland area which was 1, 55. The highest species evenness (E) was occurred in skyland and Nafri, which was 0,80 and the lowest was in PTC which was about 0,32. The highest abundance of species occurred in Skyland area was G. expansa scoring 4,9 ind/m2 and the lowest abundance in Nafri was P. nobilis scoring 1 ind/m2. The similarity index for the PTC Area, Skyland, and Nafri was on spesies of G. erosa, G. expansa, A. granosa, I. ephipium, and F. ater. Key words: Mollusca, mangrove, Youtefa bay, and Jayapura.